Beyond here and there? A description and typology of multi-transnational extended family configurations of refugees - Elisabeth K. Kraus (Genus)
Abstract The number of persons forcibly displaced across international borders increased significantly over the last decade and forced migrants’ spatial family configurations have diversified and are likely to show different patterns compared to what research has found for, e.g. labour migrants. This paper examines and disentangles the diversity of spatial family arrangements across countries of nuclear and extended family members of female and male forced migrants surveyed in Germany. Moreover, I propose a typology of refugees’ family configurations based on the whereabouts of the partner, children, parents, and siblings. The empirical analyses employ representative survey data of recent refugees from Eritrea and Syria collected in Germany in 2020. This dataset allows to account for the whereabouts of members of the nuclear as well as extended family. Descriptive statistics show the prevalence and distributions of locations of specific family members and cluster analysis is conducted to identify and propose a typology of spatial configurations of refugee families. Finally, multinomial logistic regressions are used to test associations between the obtained clusters and gender, country of origin and the financial situation, controlling for other characteristics. The findings indicate that multi-transnational family constellations beyond origin and destination countries are a common pattern among refugees, especially when considering nuclear as well as extended family members. Furthermore, different types of spatial family arrangements are related to gender and country of origin as well as family financial resources.